2021
DOI: 10.2147/amep.s280941
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students How to Interpret Chest X-Rays: The Design and Development of an e-Learning Resource

Abstract: Introduction The teaching of radiology to medical students has often been criticised for being inadequate and unstructured, with students reporting lack of confidence in assessing x-rays. In this paper, we describe how an e-learning resource, on how to interpret a chest x-ray for medical students, was designed and developed. The aim of the resource was to provide medical students with knowledge of how to interpret a chest x-ray in a systematic approach. Methods The tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Moreover, it affords the instructor the opportunity to identify the concepts and skills that proved challenging to individual medical students and attempt to effect illumination and consequently, promote mastery. [8,[13][14][15][16] Salajegeh et al [4] found out in their study that a majority of the undergraduate medical students (71.4%) felt that the E-learning package was effective in helping them learn the art of interpreting X-rays. Sait et al [14] realized that the medical students in their study were in support of this opinion when 100% of the participants agreed or strongly agreed that E-learning in Radiology was appropriate and should be recommended to other colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it affords the instructor the opportunity to identify the concepts and skills that proved challenging to individual medical students and attempt to effect illumination and consequently, promote mastery. [8,[13][14][15][16] Salajegeh et al [4] found out in their study that a majority of the undergraduate medical students (71.4%) felt that the E-learning package was effective in helping them learn the art of interpreting X-rays. Sait et al [14] realized that the medical students in their study were in support of this opinion when 100% of the participants agreed or strongly agreed that E-learning in Radiology was appropriate and should be recommended to other colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…[8,[13][14][15][16] Salajegeh et al [4] found out in their study that a majority of the undergraduate medical students (71.4%) felt that the E-learning package was effective in helping them learn the art of interpreting X-rays. Sait et al [14] realized that the medical students in their study were in support of this opinion when 100% of the participants agreed or strongly agreed that E-learning in Radiology was appropriate and should be recommended to other colleagues. Nyhsen et al [15] thought otherwise by stating that E-learning module was relatively poorly rated and should be regarded as a less effective method of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia education has been examined extensively in the pedagogical literature, resulting in recommendations on how to best design materials in order to maximise engagement and learning [13,42] While this information has informed the design of educational materials in healthcare [14][15][16][17][18][19][20][21][22][23][24][25][26][27] this has been less frequent in the MSK literature with only one RCT examining osteoarthritis-related pain, [43] and other MSK conditions being informed by narrative advice only. [28][29][30] The use of such principles [42] has not been tested in a randomized controlled trial of education for a MSK population such as adolescent idiopathic scoliosis.…”
Section: Rationalementioning
confidence: 99%
“…Many researchers are studying e-learning applications in the field of medical education ( Sait & Tombs, 2021 ; Soundy et al, 2021 ; Su et al, 2021 ; Vedi & Dulloo, 2021 ; Oropesa et al, 2022 ). The colonoscopy teaching model will inevitably develop in this direction due to digitization, networking and intelligence ( Feng et al, 2013 ; Longhini et al, 2021 ; Ouajdouni, Chafik & Boubker, 2021 ).…”
Section: Introductionmentioning
confidence: 99%